Beef cattle feedlot - Yusuf Hamali Ahmad (MARDI, Serdang, Selangor (Malaysia). Bahagian Penyelidikan Ternakan) (2013)
Feedlotting is the rearing of cattle within confined facilities in which the cattle are fattened within a specific period of time before being marketed. The facilities required for a cattle feedlot are decribed together with factors which influence both the design and location. The principles and practices of feeding programmes are emphasized. The influence of breed or its crosses on growth rate, feed efficiency and carcass production is discussed briefly. The environmental pollution of feedlots is mentioned. The animal health problems most commonly encountered in feedlots are either associated with physical injuries or metabolic in nature. The basic management requirements for most feeding operations are discussed. The economic viability of a beef cattle feedlot under Malaysian conditions is influenced by several major variables such as production cost, feed cost, feeder cost, buying and selling price of cattle.